2020
DOI: 10.1038/s41598-020-70910-5
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol use is associated with decreased brain volume in early middle age in both sexes

Abstract: the aim was to examine cross-sectional association between moderate alcohol consumption and total brain volume in a cohort of participants in early middle-age, unconfounded by age-related neuronal change. 353 participants aged 39 to 45 years reported on their alcohol consumption using the AUDit-c measure. participants with alcohol abuse were excluded. Brain MRi was analyzed using a fully automated method. Brain volumes were adjusted by intracranial volume expressed as adjusted total brain volume (aTBV). AUDIT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…We find negative associations between alcohol intake and the global IDPs for both sexes and weak evidence for interactive effects between alcohol intake and sex on the brain. These findings are similar to a recent study of early middle-aged adult moderate drinkers that showed smaller brain volumes associated with moderate alcohol consumption in both men and women 46 . The weak sex-by-alcohol interactions also comport with the findings of an earlier longitudinal study in individuals with AUD 38 ; however, other cross-sectional studies have reported greater volume deficits in women than men 48,49 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find negative associations between alcohol intake and the global IDPs for both sexes and weak evidence for interactive effects between alcohol intake and sex on the brain. These findings are similar to a recent study of early middle-aged adult moderate drinkers that showed smaller brain volumes associated with moderate alcohol consumption in both men and women 46 . The weak sex-by-alcohol interactions also comport with the findings of an earlier longitudinal study in individuals with AUD 38 ; however, other cross-sectional studies have reported greater volume deficits in women than men 48,49 .…”
Section: Discussionsupporting
confidence: 91%
“…We report a multimodal brain imaging study of 36 The negative associations between alcohol intake and total GMV and WMV are consistent with prior studies of early middle-aged 46 and older adults 28,47 . Because men consume more alcohol units per day and had larger global GMV and WMV, we further examine the effect of sex in detail.…”
Section: Discussionsupporting
confidence: 87%
“…The negative associations between alcohol intake and total GMV and WMV are consistent with prior studies of early middle-aged 46 and older adults 28 , 47 . Based on Figs.…”
Section: Discussionsupporting
confidence: 89%
“…Although alcohol use disorders are relatively rare in older adults, many older people frequently consume low to moderate amounts of alcohol 12. Recently, even moderate drinking was shown to be associated with small but significant loss of brain volume in midlife,13 supporting previous research indicating an association between low risk drinking and brain damage in older adults 2. However, it is currently unclear whether these structural changes translate into functional cognitive impairment.…”
Section: From Cradle To Gravementioning
confidence: 84%